Study of Characteristics of White Corn Birdlime Dodol in Term of Flour and Packaging - Luh Suriati; Anak Agung Made Semariyani; Maria Berkat Ina (SEAS (Sustainable Environment Agricultural Science), 2018)
Indonesia has so many traditional foods processed from corn which is a specific menu of wealth to be preserved, one of which is processed Dodol. Dodol which has been known to the public is a raw material Dodol sticky rice, sweet corn and other varieties of fruit. Dodol white corn birdlime still rarely found in the market. Nutritional content of corn grain sticky rice is no less than other corn such as levels of protein, crude fiber, fat, and carbohydrates, especially high amylopectin so characteristic Dodol produced more sticky and chewy. This study aims to investigate the characteristics of sticky white corn Dodol seen from a comparison of corn flour and glutinous rice flour as well as the use of some packaging materials. The most appropriate to produce corn Dodol most good. From the research it can be concluded that the characteristics of birdlime white corn Dodol obtained are the water content ranged from 14.03% - 17.05%, protein levels ranged between 2.51% - 4.10%, carbohydrate levels ranged between 64.73% - 71.64%, fat content ranged from 8.81% - 12.14%, ash content ranged from 1.91% - 2.47%, pH ranges between 7.02% - 7.52%, while the organoleptic assessment result (3.00% - 4.73%) with criteria rather dislike to normal. Packaging materials used in birdlime white corn Dodol is banana leaves, corn husks, and plastic. Characteristics Dodol of birdlime white corn is best in terms of the packaging material in this research is to use plastic packaging materials with a moisture content of 14.03%, 4.10% protein content, carbohydrate content of 71.64%, 12.14% fat content, ash content of 2.48%, pH of 7.52, while on the organoleptic assessment, among others: the color with a value of 4.40, the aroma of 4.47, 4.73 flavor, texture 4.27%, the highest in the overall acceptance of plastic with a value 4.53. From the results of this study suggested further research needs to be done about birdlime Dodol white corn and storage of packaging materials and to determine the shelf life thus increase the selling Dodol of birdlime white corn in the market.